Heading towards a sustainable energy transition: an analysis of the potential of renewable energies - Allauja Ayllon, Milene (2025)
Renewable energies are a fundamental solution to achieve a transition towards sustainable development. Solar, wind, biogas and hydroelectric sources have the potential to change the global energy scene by being clean, abundant and with low environmental impact, contributing to the mitigation of climate change and social well-being through a circular economy. This research investigates the social, economic and environmental benefits generated by renewable energies. To this end, a literature review was carried out to analyze the practical results of renewable energies in real environments.